Transforming Healthcare: The Rapid Rise of Artificial Intelligence Revolutionizing Healthcare Applications - Hafiz Khawar Hussain; Aftab Tariq; Ahmad Yousaf Gill; Ahsan Ahmad (CV. Multi Kreasi Media, 2022)
A new age of revolutionary applications with the potential to revolutionize patient care, diagnostics, and treatment results has been ushered in by the quick uptake of artificial intelligence (AI) in the healthcare industry. This paper gives a broad overview of the current state of artificial intelligence in healthcare, examining its ground-breaking applications in precision medicine, harnessing big data for healthcare insights, ethical considerations and adoption challenges, implementing AI solutions in healthcare settings, and future directions and implications for the evolving AI healthcare landscape. The article highlights the bright future of artificial intelligence in healthcare, including improved diagnostic capabilities, personalised medicine, remote monitoring and telemedicine, precision drug discovery, greater robotic help, and the ethical and regulatory issues that go along with these developments. The conclusion highlights the enormous potential of artificial intelligence (AI) in healthcare, as well as the necessity of responsible AI practices, collaborative efforts, ethical frameworks, and workforce training to ensure the ethical use of AI and maximize its benefits in patient care and healthcare delivery. The future of AI in healthcare holds promise for enhancing patient outcomes, optimizing resource allocation, and reshaping the healthcare system as a whole by embracing the potential and addressing the difficulties.